Directives will advance: perceptions about the applicability in newborn and pediatric context - Maria Luzia Machado Godinho; Matheus Viero Dias; Edison Luiz Devos Barlem; Jamila Geri Tomaschewski Barlem; Laurelize Pereira Rocha; Amanada Guimarães Ferreira (Universidade Federal de Santa Maria, 2018)
Aim: to know the perception of the health professionals about the applicability of the anticipated directives of will in the neonatal and pediatric context. Method: qualitative, descriptive and exploratory study, developed in pediatric and neonatal pediatric hospitalization units - of a university hospital in southern Brazil. Participated 16 professionals of the nursing and medical team. The collections took place through a semistructured interview, from September to October, 2015. A discursive textual analysis was performed. Results: Evidenced aspects that hinder the applicability of the Directives, such as: denial of death attitudes, weak communication, understanding of death as an event of a punctual nature, post hierarchy and professional instrumentalization. As facilitators, such as professional (multi) interaction, bonding and support in spirituality. Final considerations: There is a misunderstanding and unease about death and all its personal significance, reflecting the difficulty of applying the Directives in this context.